Α-Branched amines through radical coupling with 2-azaallyl anions, redox active esters and alkenes. Issue 13 (9th March 2022) - Duan, Shengzu; Zi, Yujin; Wang, Lingling; Cong, Jielun; Chen, Wen; Li, Minyan; Zhang, Hongbin; Yang, Xiaodong; Walsh, Patrick J.
Abstract : A mild method for the construction of α-branched amine derivatives is presented. SET processes between the Ni catalyst, redox active esters and 2-azaallyl anions generate azaallyl radicals and alkyl radicals that functionalize the alkenes. Abstract : α-Branched amines are fundamental building blocks in a variety of natural products and pharmaceuticals. Herein is reported a unique cascade reaction that enables the preparation of α-branched amines bearing aryl or alkyl groups at the β- or γ-positions. The cascade is initiated by reduction of redox active esters to alkyl radicals. The resulting alkyl radicals are trapped by styrene derivatives, leading to benzylic radicals. The persistent 2-azaallyl radicals and benzylic radicals are proposed to undergo a radical–radical coupling leading to functionalized amine products. Evidence is provided that the role of the nickel catalyst is to promote formation of the alkyl radical from the redox active ester and not promote the C–C bond formation. The synthetic method introduced herein tolerates a variety of imines and redox active esters, allowing for efficient construction of amine building blocks.